Developing and utilizing controlled human models of infection. Issue 49 (14th December 2017) - Porter, Chad K.; Louis Bourgeois, A.; Frenck, Robert W.; Prouty, Michael; Maier, Nicole; Riddle, Mark S.
Abstract: The controlled human infection model (CHIM) to assess the efficacy of vaccines against Shigella and enterotoxigenic Escherichia coli (ETEC) has several unique features that could significantly enhance the ability to test candidate vaccines. Despite increasing interest in these models, questions remain as to how to best incorporate them into vaccine development and how to maximize results. We designed a workshop focused on CHIM as part of the Vaccines Against Shigella and ETEC (VASE) Conference. The workshop, using the World Café method, focused on; clinical outcomes, nonclinical outcomes and model standardization. Researchers with a variety of expertise and experience rotated through each focus area and discussed relevant sub-topics. The results of these discussions were presented and questions posed to guide future workshops. Clinical endpoint discussions focused on the need for harmonized definitions; optimized attack rates; difficulties of sample collection and a need for non-stool based endpoints. Nonclinical discussions centered on evolving omics-based opportunities, host predictors of susceptibility and novel characterizations of the immune response. Model standardization focused on the value of shared procedures across institutions for clinical and non-clinical endpoints as well as for strain preparation and administration and subject selection. Participants agreed CHIMs for Shigella and ETEC vaccine development could accelerate vaccine development of a promising candidate; however, it was also appreciated that variability in the model and our limited understand of the host-pathogen interaction may yield results that could negatively impact a suitable candidate. Future workshops on CHIM are needed to ensure the optimal application of these models moving forward.